PENINGKATAN HASIL BELAJAR BIOLOGI SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) KELAS X SMA NEGERI 1 BATU HAMPAR TAHUN PELAJARAN 2015/2016 - Diah Arum Palupi; Evi Suryawati; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: the efforts in improving student learning outcomes need to be done. One of the ways that can be done is to use the cooperative learning model type NHT (Numbered Head Together) in learning. This research aims to improve the learning results of biology students of class X SMAN 1 Batu Hampar Lessons year 2015/2016 through Cooperative Model Pembelajaan type of NHT. This research was conducted in February until May 2016. This research is a research action class is done in two cycles consisting of planning, implementation, observation and reflection. The subject of research is the 30 students of class X SMAN 1 Batu Hampar. The parameters in this study adalahhasil study, which consists of absorption, ketuntasan learning, appreciation groups, student's activities and the activities of the teacher. The average absorbance on a Cycle I was 77,8%, Cycle II 82,2%. Ketuntasan student learning on a Cycle I was 73,3%, cycle II 90%. I cycle group awards all groups got a terrific group of predicates and cycle II all groups get the predicate Excellent. The average student's activities in Cycles I was 79.58% and Sikus II is 83,3%. The average teacher's activity Cycle I 89,2%, Cycle II 100%. From the results of the study it was concluded that Cooperative Learning Model Type NHT can improve the results of the study of biology students of class X SMAN 1 Batu Hampar lessons year 2015-2016.Key words: improved, the results of the study, Cooperative, NHT